Analisis Faktor yang Memengaruhi Rendahnya Minat Pasangan Usia Subur terhadap Penggunaan Metode Kontrasepsi Jangka Panjang - Rismawati Rismawati; Arini Purnama Sari (Poltekkes Kemenkes Palu, 2021)
Introduction: The coverage of the use of long term contraceptive method (MKJP) in West Bajeng District is still very low. In 2020, MKJP participants are only about 23.8% with the percentage of participants in KB implants 19.6%, IUD 1.8%, MOW 2.3% and MOP 0.03%. This study aims to determine whether the factors of age, knowledge, education, sources of information, husband's support, and Communication, Information and Education (KIE) affect the low interest in EFA towards the use of MKJP in Bajeng Barat sub-district, Gowa Regency. Methods: The research method used is quantitative research with a cross sectional study approach. The population is all active family planning acceptors. The sample is PUS who are active family planning acceptors for MKJP or non-MKJP with a total sample of 96 people. Data analysis using chi square test. Results: Only 35.4% of respondents used MKJP 35.4%. There is a significant relationship between education (p=0.013), knowledge (p<0.001), husband's support (0.003), sources of information (p=0.030), and KIE (p=0.008) with low EFA interest in using MKJP. Conclusion: Low education, lack of knowledge, no husband's support, sources of information and lack of KIE cause low interest in PUS using MKJP.